2000
DOI: 10.3354/meps199097
|View full text |Cite
|
Sign up to set email alerts
|

Short-circuit in the mangrove food chain

Abstract: Crabs of the subfamily Sesarminae are important components of mangrove ecosystems in the Indo-west Pacific, Africa, the Caribbean and South America. By retaining a large proportion of mangrove leaf-litter within mangrove forests, they profoundly influence the functioning of mangrove ecosystems. Despite obvious importance to ecosystem functioning, little is known about predation on sesarmid crabs. Three large, predatory fishes of tropical lndo-Pacific estuaries, the groupers Epinephelus coioides and E. malabari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(96 citation statements)
references
References 34 publications
4
89
0
Order By: Relevance
“…Therefore, one of the dominant fish species of tidal mangrove channels along the north Brazilian coast lives on prey of low trophic levels. This emphasizes the conclusion of Sheaves and Molony (2000) that food chains leading from mangroves to top predators are likely to be shorter than previously thought. C. psittacus have a key function in a short intertidal mangrove food web.…”
Section: Energy Flowmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, one of the dominant fish species of tidal mangrove channels along the north Brazilian coast lives on prey of low trophic levels. This emphasizes the conclusion of Sheaves and Molony (2000) that food chains leading from mangroves to top predators are likely to be shorter than previously thought. C. psittacus have a key function in a short intertidal mangrove food web.…”
Section: Energy Flowmentioning
confidence: 57%
“…The mangrove productivity is, however, not exported due to offshore migration by the fish as Sheaves and Molony (2000) assumed for a system in tropical East Australia. South of the Amazon delta, where mangroves cover more than 400 km of continuous coastline (Lacerda et al, 2000, p. 9), other complex shallow water environments such as coral reefs or sea grass beds that could motivate offshore movements of the fish are absent.…”
Section: Energy Flowmentioning
confidence: 99%
“…Indeed, Guest et al (2004) showed, using stable (δ 13 C) isotope signature of crabs as an indicator of carbon source, that carbon movement between 2 adjacent habitats (mangroves and salt marshes) in a subtropical estuary was spatially restricted to a scale of several metres (< 30 m). However, in the Indo-Pacific region, many organisms migrate into inundated mangroves at high tide to feed (Nagelkerken & Van der velde 2004) and, therefore, a substantial part of the mangrove productivity sequestered by herbivorous crabs might be exported from mangrove ecosystems as a result of tidal migration of predatory fish feeding on these crabs (Sheaves & Molony 2000). Nevertheless, the scale of this transfer of mangrove production cannot be estimated without a full understanding of the diet of the invertebrates living in the mangrove ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Although most grapsoids are opportunistic scavengers, many are essentially detritivorous as they feed on dead leaves that have fallen off the mangrove, particularly members of the family Sesarmidae, which are important components of mangrove ecosystems in the Indo-West Pacific, the African, the Caribbean and the South American coasts (Sheaves and Molony, 2000). About fifty species of sesarmid crabs have been reported to be predominantly associated with mangrove ecosystems (Islam et al, 2002).…”
Section: Introductionmentioning
confidence: 99%